Time Semantics As an expression in architecture - Ali, Khalil ibrahim; al-saady, Hadeer jassim (Iraqi Journal of Architecture and Planning, 2009)
The concept of time had stood to confront philosophical studies in several fields of kaowledge, including archilecture, demanding an understanding of this phenomenon. Time remained invisible, and only felt by sense, intuition and abstraction; unconnected to architecture as an expression of form. This paper tries to relate time to architecture not as an evolutionary concept in architectural change but as a factor which evolves with significance in expressive aspect. It presents findings, which illustrates time as a signifier to architectural vision and expression.